Associação bidirecional entre sibilância e problemas de saúde mental na adolescência: coorte de nascidos vivos de Pelotas, 1993 - Gómez Cofré, Natalia Graciela (2013)
Introduction: several studies have shown an association between wheezing and mental health problems in children and adolescents. This association can occur in both directions. Objective: to assess longitudinally the bidirectional association between wheezing and mental health problems in adolescents at 11 and 15 years of age. Methods: individuals belonging to the 1993 birth cohort, in the city of Pelotas, Brazil, were followed at 11 and 15 years old. Wheezing was assessed as presence of wheezing in the last 12 months , based on the International Study of Asthma and Allergies in Childhood (ISAAC). Mental health problems were assessed with the questionnaire Strengths and Difficulties Questionnaire (SDQ), with application version for parents. For the analysis, the total of subjects was divided in two samples from which teenagers with the outcomes (wheezing/mental health problems) at 11 years old were excluded. Results: in the crude analysis for mental health problems at age 11 as predictor of wheezing at age 15, there was a statistical significant association for both sexes: males [RI = 1.64 (95% CI 1.16, 2.31), p = 0.005], and females [RI = 1.68 (95% CI 1.28, 2.19), p <0.001]; after adjustment for confounders, the association was maintained only for females [RI = 1.66 (95% CI 1, 16, 2.36), p = 0.005]. When wheezing at age 11 was evaluated as predictor of mental health problems at 15 years old, there was a statistical significant association in the crude analysis only for boys [RI = 1.49 (95% CI 1.04, 2.16), p=0.031]; after adjusting for confounders, this association was no longer statistically significant (p = 0.652). Conclusions: girls who present mental health problems at age 11 have a high risk for developing wheezing at 15 years old.